Pre-equalization for pre-rake DS-UWB systems with spectral mask constraints - Mohsenian-Rad, Amir-Hamed; Mietzner, Jan; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Communications, 2011)
In this paper, we propose a novel optimization-based pre-equalization filter (PEF) design framework for direct-sequence ultra-wideband (DS-UWB) systems with pre-Rake combining. The key feature in our design is that we explicitly take into account the spectral mask constraints that are usually imposed in practice by the telecommunications regulation and standardization bodies. This avoids the need for an inefficient power back-off, which is necessary for the existing pre-Rake-based transmitter structures designed solely based on average transmit power constraints. We consider two PEF design structures. In the first structure, the PEF is placed before the up-sampling unit at the transmitter. In the second structure, the PEF is placed after the up-sampling unit. We show that these two structures are significantly different in terms of their capabilities in reducing the residual inter-symbol interference at the receiver and also in following the spectral mask at the transmitter. This introduces a trade-off such that one design structure outperforms the other one, depending on the system parameters. In this regard, we show that if the spreading factor is large enough, the second design structure has a superior performance. Simulation results confirm that both of the proposed PEF structures lead to significant performance gains over PEF designs without explicit spectral mask considerations. In addition, our PEF designs have the capability of adhering to spectral masks with arbitrary shapes. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: inter-symbol interference; optimization; pre-equalization; pre-Rake combining; semi-definite programming; Spectral mask constraints; ultra-wideband communication